A simple and sensitive flow injection method based on the catalytic activity of CdS quantum dots in an acidic permanganate chemiluminescence system for determination of formaldehyde in water and wastewater. Issue 4 (2nd March 2016) - Khataee, Alireza; Lotfi, Roya; Hasanzadeh, Aliyeh; Iranifam, Mortaza
Abstract : The intensity of emitted light from KMnO4 –HCHO–CdS QDs system is linearly proportional to HCHO concentration. Abstract : A simple and sensitive flow injection chemiluminescence (CL) method in which CdS quantum dots (QDs) enhanced the CL intensity of a KMnO4 –formaldehyde (HCHO) reaction was offered for the determination of HCHO. This CL system was based on the catalytic activity of CdS QDs and their participation in the CL resonance energy transfer (CRET) phenomenon. A possible mechanism for the supplied CL system was proposed using the kinetic curves of the CL systems and the spectra of CL, photoluminescence (PL) and ultraviolet-visible (UV–Vis). The emanated CL intensity of the KMnO4 –CdS QDs system was amplified in the presence of a trace level of HCHO. Based on this enhancement effect, a simple and sensitive flow injection CL method was suggested for the determination of HCHO concentration in environmental water and wastewater samples. Under selected optimized experimental conditions, the increased CL intensity was proportional to the HCHO concentration in the range of 0.03–4.5 μg L −1 and 4.5–10.0 μg L −1 . The detection limits (3 σ ) were 0.0003 μg L −1 and 1.2 μg L −1 . The relative standard deviations (RSD%) for eleven replicate determinations of 4.0 μg L −1 HCHO were 2.2%. Furthermore, the feasibility of the developed method was investigated via the determination of HCHO concentration in environmental water and wastewater samples.